Optimization of Profit-Sharing Financing at Islamic Banking in Indonesia - Riyadi, Selamet; Iqbal, Muhammad; Pangastuti, Annisa Arifah; Muditomo, Arianto (University of Merdeka Malang, 2021)
The purpose of this study is to identify factors that can encourage an increase in profit- sharing financing. These factors are third-party funds in the form of mudharabah deposits, non-performing financing, equivalent rate, operational efficiency ratio, economic growth, and inflation. The research method uses a co-integration and error correction model (ECM) with a sample of the Islamic banking industry in Indonesia from the first quarter of 2015 to the third quarter of 2020. The results show that the factors that encourage profit-sharing financing are the growth of third-party funds in the form of mudharabah deposits, non- performing low funding, low equivalent rate, operational efficiency, and economic growth. These factors are the key to driving the growth of profit-sharing financing. This research contributes to providing various alternative strategies in encouraging the growth of profit- sharing financing, such as increasing retained earnings from profit, providing attractive profit-sharing incentives, transparency of financial reports to attract people to invest in Islamic banks, prevention and supervision of non-performing financing, be careful in determining the ratio by taking into account several internal and external aspects, as well as paying attention to the movements of existing economic growth. DOI : https://doi.org/10.26905/jkdp.v25i2.5212